Comparative Study of the Islamic Education Concepts of Imam Al-Ghazali and Al-Farabi - Rusdiyanto, Rusdiyanto; Werdiningsih, Indah (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3183, 2024)
Islamic education today is deeply rooted in historical intellectual developments, particularly influenced by prominent philosophers like Imam Al-Ghazali and Al-Farabi. The classical period saw significant contributions from these figures, forming the foundation for both modern and contemporary interpretations of Islamic educational thought. This research utilizes a literature review to explore and compare the educational philosophies of Al-Ghazali and Al-Farabi, examining their core principles and objectives. Al-Ghazali’s educational philosophy emphasizes the pursuit of virtue and obedience to Allah, prioritizing spiritual development over worldly success. He advocates for a curriculum that fosters moral discipline and religious devotion, ensuring that education serves as a means to cultivate a close relationship with God. In contrast, Al-Farabi views education as a means to acquire values, knowledge, and practical skills, ultimately guiding individuals toward perfection by integrating intellectual and ethical development. His curriculum focuses on a broad range of sciences, including metaphysics, mathematics, and natural sciences, aiming to equip individuals with the tools necessary for both personal and societal advancement. The comparative analysis reveals both differences and similarities: Al-Ghazali focuses on spiritual and moral education, while Al-Farabi highlights intellectual and practical skills as key to human perfection. Despite their differing approaches, both philosophers contribute valuable perspectives to the broader discourse on Islamic education and its evolving paradigms. In conclusion, Al-Ghazali and Al-Farabi offer distinct yet complementary approaches to Islamic education. Al-Ghazali’s emphasis on morality and spiritual obedience contrasts with Al-Farabi’s focus on intellectual growth and practical application, together providing a comprehensive understanding of Islamic educational goals. This study enriches the ongoing discourse on integrating spiritual, moral, and intellectual development within Islamic education, highlighting the enduring relevance of their philosophies in shaping contemporary educational practices.